ANALYSIS OF SOCIAL FAIRNESS IN THE HISTORY OF HUMANITY CONTEMPLATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article analyzes the views of the ancient philosophers Plato and Aristotle on political justice. The essence of the content of Plato's view of moral justice is revealed. And also special attention is paid to the concepts of moral justice and the state system analyzed by Plato. The views of Aristotle on the principle of equality are studied from a philosophical point of view. The meaning of the concept of social justice and its place in human life are revealed. It was revealed that the comprehensive reforms carried out in our country are based on the principle of justice.